2018
DOI: 10.12816/0044354
|View full text |Cite
|
Sign up to set email alerts
|

Eosinopenia as a Diagnostic Marker of Sepsis in Critically Ill Patients

Abstract: Background: sepsis refers to the presence of a serious infection that correlates with systemic and uncontrolled immune activation. Few studies had analyzed eosinophil count as a prognostic marker of outcome in patients with infection. Eosinopenia is an interesting biomarker because the eosinophil count is always measured in clinical practice and the additional costs would therefore be negligible.The aim of this wrk: this studyaimed to test the value of eosinopenia in the diagnosis of sepsis in critically ill p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…They found that admission eosinophil counts of <50 cells/mm 3 could be used as a predictor for sepsis diagnosis in ICU patients, although the admission eosinophil sensitivity and specificity did not predict mortality. 18 In another study by Swaminathan et al, the absolute eosinophil count was a reliable marker of mortality in patients with perforative peritonitis, as the values decreased in patients who did not survive. 19 Acute exacerbation of chronic obstructive pulmonary disease is frequently seen in emergency departments.…”
Section: Discussionmentioning
confidence: 94%
“…They found that admission eosinophil counts of <50 cells/mm 3 could be used as a predictor for sepsis diagnosis in ICU patients, although the admission eosinophil sensitivity and specificity did not predict mortality. 18 In another study by Swaminathan et al, the absolute eosinophil count was a reliable marker of mortality in patients with perforative peritonitis, as the values decreased in patients who did not survive. 19 Acute exacerbation of chronic obstructive pulmonary disease is frequently seen in emergency departments.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, eosinopenia may represent an excellent marker for the diagnosis of bacterial sepsis. [5][6][7]11,12,15 The study by Gil in 2003 showed that sepsis was strongly correlated with an eosinophil count <40 cells/mm 3 and WBC count >10,000 cells/mm 3 with specificity and PPV of 100% and related to bacterial infectious diseases. 15 Abidi's study in 2008 showed that eosinopenia (cut-off value of ≤ 50 cells/mm 3 ) could be used as sepsis marker in patients hospitalized in the ICU with a sensitivity of 80% and specificity of 91%.…”
Section: Discussionmentioning
confidence: 99%
“…As a cheap and always measured test, eosinopenia offers a higher reliability than other hematology markers of infection such as leucocytosis and neutrophilia. [4][5][6]19 In acute…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations